Strategi Analisis Maharah Qira’ah untuk Pemahaman Bahasa Arab di Madrasah Aliyah Al-Masduqiyah (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to analyze the implementation of short text analysis strategies in Maharah Qira’ah to enhance Arabic language comprehension at Madrasah Aliyah Al-Masduqiyah Patokan Kraksaan. Maharah Qira’ah, as one of the core skills in Arabic language learning, requires a deep understanding of language structures and text meanings. Therefore, short text analysis strategies are applied as a method to strengthen students’ understanding of vocabulary, grammar, and contextual meaning in Arabic texts. This research employs a descriptive qualitative approach with data collection techniques, including observation, interviews, and documentation. The findings indicate that using short texts in Maharah Qira’ah instruction has a positive impact on students' comprehension, particularly in word meaning interpretation, sentence structure understanding, and critical thinking skills. However, the study also identifies several challenges, such as students' limited vocabulary, text difficulty levels, and insufficient teaching resources. By understanding the benefits and challenges, this strategy can be further developed through more innovative approaches, such as digital media utilization and the integration of contextual learning methods in Arabic language instruction. This study is expected to contribute to the development of Arabic language teaching methods at the Madrasah Aliyah level.